No clear survival benefit of azacitidine for lower‐risk myelodysplastic syndromes: A retrospective study of Nagasaki. Issue 12 (23rd October 2020) - Toriyama, Eo; Hata, Tomoko; Yokota, Ken‐ichi; Chiwata, Masahiko; Kamijo, Rena; Hashimoto, Miki; Taguchi, Masataka; Horai, Makiko; Matsuo, Masatoshi; Matsuo, Emi; Takasaki, Yumi; Kawaguchi, Yasuhisa; et al.
Abstract: The efficacy of azacitidine (AZA) on survival of lower risk (LR) ‐ myelodysplastic syndromes (MDS) is controversial. To address this issue, we retrospectively evaluated the long‐term survival benefit of AZA for patients with LR‐MDS defined by International Prognostic Scoring System (IPSS). Using data from 489 patients with LR‐MDS in Nagasaki, hematologic responses according to International Working Group 2006 and overall survival (OS) were compared among patients that received best supportive care (BSC), immunosuppressive therapy (IST), erythropoiesis‐stimulating agents (ESA), and AZA. Patients treated with AZA showed complete remission (CR) rate at 11.3%, marrow CR at 1.9%, and any hematologic improvement at 34.0%, with transfusion independence (TI) of red blood cells in 27.3% of patients. and platelet in 20% of patients, respectively. Median OS for patients received IST, ESA, BSC, and AZA (not reached, 91 months, 58 months, and 29 months, respectively) differed significantly ( P  < .001). Infection‐related severe adverse events were observed in more than 20% of patients treated with AZA. Multivariate analysis showed age, sex, IPSS score at diagnosis, and transfusion dependence were significant for OS, but AZA treatment was not, which maintained even response to AZA, and IPSS risk status at AZA administration was added as factors. We could not find significant survival benefit of AZA treatment for LR‐MDS patients. Abstract : Multivariate analysis showed age, sex, IPSS score at diagnosis, and transfusion dependence were significant for OS, but AZA treatment was not, which maintained even response to AZA, and IPSS risk status at AZA administration was added as factors. We could not find significant survival benefit of AZA treatment for LR‐MDS patients.